URGENSI PENERAPAN KETENTUAN PASAL 33 AYAT (1) UNITED NATIONS CHARTER (PIAGAM PBB) DALAM PENYELESAIAN KONFLIK TAIWAN DAN CHINA - Muhammad Akbar Fauzan Aziz; Arlina Permanasari (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2021)
The dynamics of the conflict between China and Taiwan have not yet been resolved. Internationallaw as a legal norm that is recognized and applied internationally has an important role inresolving disputes that arise between countries. The provisions of international law haveprohibited the use of anxiety in relations between countries, China as a country that dominatesthe recognition of sovereignty from 171 other countries considers that this matter is an internalproblem of their own country which is sought to be resolved peacefully, based on the provisionsof Article 33 Paragraph (1) of the United Nations settlement The peaceful dispute is resolved bynegotiation, investigation, mediation, conciliation, arbitration, and legal settlement throughregional bodies or arrangements, or other peaceful means chosen. It is hoped that the urgencyof the provisions of the article will create peace, world security, encourage brotherly relations between nations, and become the center of alignment of all joint actions against countries thatendanger world peace.